2004
DOI: 10.1038/sj.leu.2403577
|View full text |Cite
|
Sign up to set email alerts
|

Reply to Stams et al

Abstract: ER, Janka-Schaub GE et al. Expression levels of TEL, AML1 and the fusion products TEL-AML1 and AML1-TEL versus drug sensitivity and clinical outcome in t(12;21) positive pediatric ALL. submitted. 6 Hubner S, Cazzaniga G, Flohr T, van der Velden VH, Konrad M, Potschger U et al. High incidence and unique features of antigen receptor gene rearrangements in TEL-AML1-positive leukemias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Our results contradict those reported by both Stams et al (2003) and Krejci et al (2004) in that AS mRNA levels in NPBMC were found to be significantly higher than those in lymphoblasts, in line with the expectation from many in vitro studies. As previously discussed (Krejci et al , 2005a,b, Stams et al , 2005) this may be due to the choice of the endogenous control used to normalise AS expression. We selected TBP as a suitable control as the variation of TBP expression between samples of lymphoid origin has been shown to be lower than either GAPDH or β 2microglobulin (Lossos et al , 2003) and, in our RQ RT‐PCR assay, the abundance of TBP was similar to that of AS .…”
Section: Resultsmentioning
confidence: 99%
“…Our results contradict those reported by both Stams et al (2003) and Krejci et al (2004) in that AS mRNA levels in NPBMC were found to be significantly higher than those in lymphoblasts, in line with the expectation from many in vitro studies. As previously discussed (Krejci et al , 2005a,b, Stams et al , 2005) this may be due to the choice of the endogenous control used to normalise AS expression. We selected TBP as a suitable control as the variation of TBP expression between samples of lymphoid origin has been shown to be lower than either GAPDH or β 2microglobulin (Lossos et al , 2003) and, in our RQ RT‐PCR assay, the abundance of TBP was similar to that of AS .…”
Section: Resultsmentioning
confidence: 99%
“…l ‐Asparaginase ( l ‐Asnase) obtained from Escherichia coli is a kind of enzyme that can hydrolyze l ‐asparagine ( l ‐Asn) and l ‐glutamine ( l ‐Gln) to l ‐aspartic acid and l ‐glutamic acid ( l ‐Glu), respectively. Due to its rapid depletion of l ‐Asn and suppression effect in the growth of malignant cells, l ‐Asnase can be employed as an important drug for the treatment of acute lymphoblastic leukemia (ALL) . However, the control efficacy of l ‐Asnase is limited due to its cytotoxic effect and the secondary complications, including coagulation abnormalities, hepatic, and pancreatic dysfunction .…”
Section: Introductionmentioning
confidence: 99%
“…Since 1967, L-asparaginase (L-Asnase) has been used as an integral part of the treatment of child ALL. 1 It can catalyze the hydrolysis of L-asparagine (L-Asn) to L-aspartic acid (L-Asp) and ammonia. Thus, the relative deficiency of L-Asn in the serum and endogenous L-Asn synthesis could cause the apoptosis and impair protein synthesis in leukemic blasts.…”
Section: Introductionmentioning
confidence: 99%
“…2 Results showed that L-Asnase could cause complete remission in 40-60% of paediatric ALL cases when it was used alone. 1 Although L-Asnase is effective in the treatment of malignant diseases, many side effects, including hepatic toxicity, allergic reaction, pancreatitis, central nervous system toxicity and decreased synthesis of blood clotting factors, have been reported about this standard chemotherapy component for ALL. 3 It was well documented that L-Asnase was the leading cause of hypersensitivity reactions in 5 to 45% of the patients 4 and thrombotic events varying from 1.1 to 73% in children.…”
Section: Introductionmentioning
confidence: 99%